2004
DOI: 10.2111/1551-5028(2004)057[0574:vcayog]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Change After 65 Years of Grazing and Grazing Exclusion

Abstract: The Nevada Plots exclosure system was constructed in 1937 following passage of the Taylor Grazing Act to assess long-term effects of livestock grazing on Nevada rangelands. A comparison of vegetation characteristics inside and outside exclosures was conducted during 2001 and 2002 at 16 sites. Data analysis was performed with a paired t test. Out of 238 cover and density comparisons between inside and outside exclosures at each site, 34 (14% of total) were different (P < 0.05). Generally, where differences occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 16 publications
5
19
1
5
Order By: Relevance
“…This result is in line with reports from savannah (Jeltsch et al 1997;Wiegand et al 2000;Tobler et al 2003;Courtois et al 2004) and forested (Motta 2003;Weisberg and Bugmann 2003) regions, reporting deleterious cattle effects on the sustainability of the vegetation. The regeneration failure suggested by our results may result from direct effects of foraging activity like herbivory and trampling (Torres 1983;Augustine and McNaughton 1998), or indirect effects like increased microclimatic effects of abrupt edges facing pastures (Murcia 1995).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in line with reports from savannah (Jeltsch et al 1997;Wiegand et al 2000;Tobler et al 2003;Courtois et al 2004) and forested (Motta 2003;Weisberg and Bugmann 2003) regions, reporting deleterious cattle effects on the sustainability of the vegetation. The regeneration failure suggested by our results may result from direct effects of foraging activity like herbivory and trampling (Torres 1983;Augustine and McNaughton 1998), or indirect effects like increased microclimatic effects of abrupt edges facing pastures (Murcia 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Cattle use forest fragments for shelter, shade, forage (Torres 1983) and water (Squires 1974). Although cattle impacts on savannah vegetation has received considerable attention (Jeltsch et al 1997;Wiegand et al 2000;Tobler et al 2003;Courtois et al 2004), and despite cattle grazing being a widespread activity in humid Neotropics, few studies have tried to evaluate the impacts of cattle ranching on tropical or subtropical tree populations in forest fragments. Trampling and herbivory by the ungulates may have an important impact on the size and age structure of populations (Johnson and Fryer 1989;Sullivan et al 1995;Gómez-Aparicio et al 2004;Abrams et al 1995;Zackrisson et al 1995;Santos and Souza 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Many earlier studies on the effects of large herbivores on community composition can be criticized on the basis of poor replication (but see Courtois et al 2004); our inferences are based on more replicated exclosures within shrublands than in any previous work. It is also possible that earlier work failed to allow enough time for the effects of herbivore exclusion to emerge.…”
Section: Grazing Effects On Plant Covermentioning
confidence: 89%
“…Stohlgren et al (1999) reported similar findings from studies of semiarid grasslands and shrub steppe in the Rocky Mountains-shrub cover increased within exclosures while bare ground and herbaceous cover were largely unaffected by elimination of grazing. Other studies in similar habitats have also shown that cessation of grazing can increase the cover of shrubs (e.g., Schultz and Leininger 1990;Coughenour 1991;Singer 1996;Anderson and Inouye 2001) and forbs (Reardon 1996) while exerting nominal or no effects on net herbaceous cover (Coughenour 1991, Courtois et al 2004). Our observations were made in a dry year, which might account for the absence of detectable effects on grass cover, because herbaceous species cover is highly responsive to precipitation patterns (Fahnestock and Detling 1999;Ludwig et al 2000;Anderson and Inouye 2001).…”
Section: Grazing Effects On Plant Covermentioning
confidence: 89%
“…In recent years, intensive studies have presented the effects and protective benefits of PSC or grazing exclusion on aboveground vegetation succession and community structure (Courtois et al, 2004;Gibson et al, 2001;Herrera-Arrieta et al, 2011;Loydi et al, 2012;Pettit et al, 1995;Shapotou Desert Research Experiment Station, 1991;Zhang et al, 2004;Zhao et al, 2008). However, very little quantitative research has focused on the effects of PSC and grazing exclusion on soil chemical properties or the effectiveness of restoration methods, especially in areas subjected to different degrees of degradation.…”
Section: Introductionmentioning
confidence: 99%